2016
DOI: 10.1051/0004-6361/201425196
|View full text |Cite
|
Sign up to set email alerts
|

Wide-band, low-frequency pulse profiles of 100 radio pulsars with LOFAR

Abstract: Context. LOFAR offers the unique capability of observing pulsars across the 10−240 MHz frequency range with a fractional bandwidth of roughly 50%. This spectral range is well suited for studying the frequency evolution of pulse profile morphology caused by both intrinsic and extrinsic effects such as changing emission altitude in the pulsar magnetosphere or scatter broadening by the interstellar medium, respectively. Aims. The magnitude of most of these effects increases rapidly towards low frequencies. LOFAR … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
43
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(49 citation statements)
references
References 79 publications
(122 reference statements)
5
43
1
Order By: Relevance
“…This is different from what is generally observed in normal pulsars (see e.g. Thorsett 1991;Xilouris et al 1996;Pilia et al 2016), and may result from a small radio emission region in the very compact magnetospheres of MSPs. Kramer et al (1998) also show that MSPs are somewhat less luminous and less efficient radio emitters than normal pulsars, with isolated MSPs being even less luminous than their binary counterparts.…”
Section: Introductioncontrasting
confidence: 96%
“…This is different from what is generally observed in normal pulsars (see e.g. Thorsett 1991;Xilouris et al 1996;Pilia et al 2016), and may result from a small radio emission region in the very compact magnetospheres of MSPs. Kramer et al (1998) also show that MSPs are somewhat less luminous and less efficient radio emitters than normal pulsars, with isolated MSPs being even less luminous than their binary counterparts.…”
Section: Introductioncontrasting
confidence: 96%
“…We should note that the pulsar population represented in this census is biased by the selection method, essentially based on the previous detections of (Stovall et al 2015;Pilia et al 2016;Kondratiev et al 2016;Bilous et al 2016). It does not take into account pulsars that have not been detected in the HBA range.…”
Section: Resultsmentioning
confidence: 99%
“…B0611+22 and B0656+14 were previously reported as a detections with flux densities (Izvekova et al 1981, 180 mJy and 60 mJy at 85 MHz respectively), which are compatible with our upper limits of 337 mJy and 77 mJy. We expected to detect J0921+6254 (detected in Pilia et al 2016, but with no measured flux density). The pulsar was detected by the LOFAR core LBA census (Bilous et al 2019) with a mean flux density of 41±22 mJy, which is consistent with our upper limit of 58 mJy.…”
Section: Upper Limits For Non-detectionsmentioning
confidence: 89%
See 1 more Smart Citation
“…The study highlighted the importance of low-frequency study of polarisation properties to probe both the effects of pulsar magnetosphere and the interstellar medium that are more pronounced. Pilia et al (2016) studied the pulse profiles of 100 pulsars with the LOFAR HBAs at frequencies of 120−167 MHz and 26 pulsars with the LOFAR Low Band Antennas (LBAs) at frequencies of 15−62 MHz, and compared them with archival observations at 350 and 1400 MHz. They found that the frequency evolution of most of the pulsars follow the radius-frequency-mapping model (RFM model, Ruderman & Sutherland 1975;Cordes 1978), where the width of the pulse profile of a pulsar increases with decreasing observing frequency.…”
mentioning
confidence: 99%